Awareness, knowledge, and beliefs about probiotics and prebiotics among Saudi adults: a cross-sectional study - Alkhaldy, Areej Ali (Frontiers in Immunology, 2024)
Background: Probiotics and Prebiotics are essential for supporting both overall health and gastrointestinal health. However, the perception of these dietary components among the general public in Saudi Arabia is not well understood. The purpose of this study was to evaluate public awareness, knowledge, and beliefs regarding prebiotics and probiotics across Saudi Arabia.Our cross-sectional study included 1,306 participants aged 18 years and above. Data were collected in Saudi Arabia between May and July 2023 using a self-administered online questionnaire via convenience sampling.Results: A high level of awareness was self-reported by only 21.9% of participants, whereas more than half (51.8%) of participants rated their level of awareness as low. Overall, 37.5% of participants displayed a high level of knowledge about probiotics and prebiotics, whereas 15.5% had a low level of knowledge. The majority of participants believed in the beneficial effects of probiotics and prebiotics on overall digestion/gut health (84.1%) and supporting the immune system (72.5%). However, less than half of participants believed in their beneficial effects on overweight/obesity (42.3%), stress management (35%), mental health/stress (29.2%), and heart health (28.7%).The obtained findings indicate sufficient levels of knowledge about prebiotics and probiotics among a population sample of Saudi adults. However, enhanced educational efforts and optimized strategies for promoting a comprehensive awareness and understanding of probiotics and prebiotics are recommended.